Design Media Interactive Digital Based on Oral Arts Aceh Meurukon as Preserving Intangible Cultural Heritage in the Era Of Society 5.0 - Elfina Elfina; Cut Santika; Muhammad Darwis; Venni Arviani; M. Kasir (CV Putra Publisher, 2026)
Acehnese oral tradition Meurukon is an intangible cultural heritage that embodies significant historical, religious, and educational values for Acehnese society. However, its existence has declined considerably due to the decreasing interest of younger generations, shifting communication patterns, and the dominance of global digital culture. This study aims to analyze the current existence of Meurukon, identify the need for digital-based cultural preservation media, and develop an interactive digital medium based on Meurukon as a strategy for cultural preservation in the Society 5.0 era. The study employed a Research and Development (R&D) approach using the 4D model consisting of define, design, develop, and disseminate stages. Data were collected through questionnaires, interviews, expert validation, and user trials involving 50 respondents comprising students, university students, and Acehnese cultural figures in Bireuen Regency. The findings revealed that the existence of and youth interest in Meurukon remain low, while the demand for interactive digital media is very high. The developed media achieved a feasibility score of 86.25% categorized as highly feasible and received a positive user response rate of 87%. These findings indicate that Meurukon-based interactive digital media effectively supports the preservation of local culture through a more adaptive, interactive, and sustainable approach in the digital era